Loss Control in Southeast Asia: The Impact of Depopulation in Japan - Agil Kurniadi; Roby Rakhmadi (Jurnal Terekam Jejak, 2025)
This article discussed the impact of depopulation in Japan that influencing Southeast Asia. The phenomena of depopulation are dangerous problem, but many people didn’t notice. In case of Japan, having economical power in Southeast Asia, it can potentially lose control of economy. Depopulation can make the Japan power decrease economically. China even be superior to Japan as the state with overpopulated people in economical rivalry. Depopulation as one of the factors that make Japan loss control can be estimated as important factor. This article used qualitative methods, supported by statistic and literature data. By the article, it can be concluded that the problem of depopulation as an issue is not cheap issue, but its significant and dangerously. The case of Japan can be a good review for analyzing negative impacts.